Pengaruh Kebiasaan Merokok Orang Tua terhadap Perilaku Merokok Remaja di Indonesia - Novi Utami (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Smoking is a risk factor for infectious diseases such as asthma, chronic obstructive pulmonary disease, lung cancer, hypertension, coronary heart disease, heart failure, and stroke. Nowadays, smoking behavior is not only found among adults but has become a lifestyle for some teenagers in Indonesia. This study aims to study how the influence of smoking behavior on parents on the smoking behavior of adolescents aged 15-24 years in Indonesia. This study used a cross-sectional study design of 4,959 adolescents aged 15-24 years as a result of the 2014 IFLS who were single. The analysis used contains a descriptive analysis and inference. The majority of teen smokers are light smokers who smoke a maximum of 10 cigarettes per day and most start smoking at the age of 12 to 17 years. The results of the analysis using binary logistic regression showed that smoking behavior in parents significantly affected adolescent smoking behavior (p=0.000; OR=1.397; 95% CI=1.173 <OR<1.663). Gender and age groups also influence smoking behavior in adolescents. Meanwhile, the classification of residence was not significant for adolescent smoking behavior (p=0.337; OR=0.920; 95% CI=0.777<OR <1.090). Efforts to prevent teenage smoking habits should be more focused on children who live with smokers' parents.